The vascular anatomy of the ovary and the relative contribution of the ovarian and uterine arteries to the blood supply of the ovary in the guinea-pig. - Hossain, M I (1983)
Guinea-pig ovaries were supplied by paired ovarian arteries which on both sides were in close apposition to the corresponding ovarian veins along their course, and which formed end-to-end anastomoses with the cranial ends of the uterine arteries. A total of three or four spirally coiled branches of the ovarian artery entered the ovarian hilus and branched within the ovary to supply both cortex and medulla. Usually, each Graafian follicle and corpus luteum was supplied by a single arterial branch from one of the cortical vessels. The veins were less coiled than the arteries. One or occasionally two veins drained each corpus luteum. Several large veins draining each ovary joined to form a single ovarian vein, which finally joined the caudal vena cava on the right side and the left renal vein on the left side. The direction of blood flow in the utero-ovarian arterial anastomosis was studied by direct visual observation in anaesthetised guinea-pigs; blood flowed towards the uterus in all observations on all guinea-pigs studied. The functional significance of the above observations is discussed.